Existence of Homoclinic Orbits for a Singular Differential Equation Involving p-Laplacian - Honghui Yin; Bo Du; Qing Yang; Feng Duan (Journal of Function Spaces)
The efficient conditions guaranteeing the existence of homoclinic solutions to second-order singular differential equation with p-Laplacian ϕpx′t′+fx′t+gxt+ht/1−xt=et are established in the paper. Here, ϕps=sp−2s,p>1,f,g,h,e∈Cℝ,ℝ with ht+T=ht. The approach is based on the continuation theorem for coincidence degree theory.